Genomic testing and counseling: The contribution of next‐generation sequencing to epilepsy genetics. (13th June 2020) - Alsubaie, Lamia; Aloraini, Taghrid; Amoudi, Manal; Swaid, Abdulrahman; Eyiad, Wafaa; Al Mutairi, Fuad; Ababneh, Farouq; Alrifai, Muhammad Talal; Baarmah, Duaa; Altwaijri, Waleed; Alotaibi, Naser; Harthi, Ashraf; et al.
Abstract: Introduction: Currently, next‐generation sequencing (NGS) technology is more accessible and available to detect the genetic causation of diseases. Though NGS technology benefited some clinical phenotypes, for some clinical diagnoses such as seizures and epileptic disorders, adaptation occurred slowly. The genetic diagnosis was mainly based on epilepsy gene panels and not on whole exome and/or genome sequencing. Method: We retrospectively analyzed 420 index cases, referred for NGS over a period of 18 months, to investigate the challenges in diagnosing epilepsy. Result: Of the 420 cases, 65 (15%) were referred due to epilepsy with one third having a positive family history. The result of the NGS was 14 positive cases (21.5%), 16 inconclusive cases (24%), and 35 (53%) negative cases. No gene has been detected twice in the inconclusive and positive groups. Comparative genomic hybridization has been performed for all 30 NGS negative cases and four cases with pathogenic variants (deletion in 15q11.213.1, deletion of 2p16.3, deletion in Xq22.1, and deletion in 17p13.3) were identified. Conclusion: These findings have implications for our understanding of the approach to genetic testing and counseling of patients affected with seizures and epilepsy disorders. The overall diagnostic yield of exome/genome sequencing in our cohort was 23%. The main characteristic is genetic heterogeneity, supporting NGS technology as a suitable testing approach for seizures and epilepsy disorders. Genetic counseling for newly identified disease‐causing variants depends on the pedigree interpretation, within the context of disease penetrance and variable expressivity.